Assessment of economic and environmental impacts of two typical cotton genotypes with contrasting potassium efficiency1. Issue 3 (21st May 2013) - Yanshu, Hao; Xiaoli, Wang; Ying, Xia; Lishu, Wu; Cuncang, Jiang
Abstract It is essential to produce optimal crop yields while reducing adverse environmental impacts of overfertilization. Therefore, nutrient‐efficient plants may play a major role in improving the efficiency of fertilizer use whilst increasing crop yields. This field trial was conducted to study the differences on absorption and utilization of nitrogen (N), phosphorus (P), and potassium (K) of K‐efficient cotton genotype 103 and K‐inefficient cotton (Gossypium hirsutum L.) genotype 122 and their environmental and economic effects. The results show that seed cotton yield was significantly different between K‐efficient cotton genotype 103 and K‐inefficient cotton genotype 122; the yields of genotype 103 were 39.2%, 33.8%, and 25.0% higher than those of genotype 122 with no K fertilizer (K0), 112 kg K ha–1 K (K1), and 224 kg K ha–1 (K2), respectively. Even when no K fertilizer was applied, the yield of genotype 103 was still 7.9% higher than the yield of genotype 122 at the highest K level (K2). Further economic benefit analysis revealed that the value cost ratio (VCR) of genotype 103 was significantly higher than 122 at K0 and K1, and harvest index (HI) of genotype 103 was significantly higher than that of genotype 122 at all three K levels. In addition, when fertilized with K, partial factor productivity of applied K (PFPK) of genotype 103 was dramatically higher than that of genotype 122, demonstrating that genotype 103 had stronger ability to utilize K. Besides, the N‐ and P‐use efficiencies of genotype 103 were also higher than those of genotype 122. It is concluded that: (1) genotype 103 gives better profit than genotype 122 and (2) genotype 103 uses fertilizer more efficiently and reduced fertilizer inputs will alleviate environmental risks.